A STUDY ON THE POTENTIAL OF CHINA’S EXPORT TRADE OF AGRICULTURAL PRODUCTS TO THE TEN ASEAN COUNTRIES ---NEW EVIDENCE FROM THE PANEL CS-ARDL MODEL - Yantong He (PEOPLE: International Journal of Social Sciences, 2024)
This paper constructs a Panel CS-ARDL model using annual data for China and 10 ASEAN countries during the period from 2002 to 2022 to study the long- and short-term trade potentials and impacts of China's exports of agricultural products to the 10 ASEAN countries, and measures the trade potential value of China's exports to the 10 ASEAN countries with reference to the existing literature. The study shows that the trade value of agricultural exports is significantly positively correlated with China's GDP, ASEAN's GDP, and ASEAN's population, while it is significantly negatively correlated with China's population, and the results are consistent in the short and long term. After measuring the trade potential value, it is found that China's agricultural export potential to the ten ASEAN countries is overall better, but it is characterized by uneven distribution and unbalanced development. Among them, the trade potential value of Indonesia fluctuates greatly, and the trade potential of Malaysia gradually reaches saturation.